2003
DOI: 10.1161/01.str.0000053851.17964.c6
|View full text |Cite
|
Sign up to set email alerts
|

Family History and Risk of Subarachnoid Hemorrhage

Abstract: Background and Purpose-We sought to examine the relation between a family history of subarachnoid hemorrhage (SAH) and the risk of SAH by using a case-control study. Methods-Case subjects consisted of a consecutive series of 195 patients with spontaneous SAH, aged 30 to79 years, with aneurysms confirmed by angiography and/or CT scan. Hospital and community control subjects were identified and matched to each case by sex and age (Ϯ2 years). Multiple conditional logistic regression was used to calculate the odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 47 publications
(42 reference statements)
0
27
0
2
Order By: Relevance
“…Our methods were described previously in detail (Okamoto et al, 2001(Okamoto et al, , 2003Okamoto and Horisawa, 2006). Briefly, we recruited all consecutive and incident SAH patients admitted at two large medical hospitals located in Nagoya from April 1992 to March 1997.…”
Section: Methodsmentioning
confidence: 99%
“…Our methods were described previously in detail (Okamoto et al, 2001(Okamoto et al, , 2003Okamoto and Horisawa, 2006). Briefly, we recruited all consecutive and incident SAH patients admitted at two large medical hospitals located in Nagoya from April 1992 to March 1997.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Furthermore, several studies suggested an increased occurrence of IA and SAH in first-and second-degree relatives of SAH, with the incidence rate of 6-10%. [6][7][8][9] Several Mendelian disorders, such as autosomal-dominant polycystic kidney disease and Ehlers-Danlos syndrome type IV are associated with an increased risk of IA formation. 10,11 All these evidence fortified the roles of genetic factors in the pathogenesis of IA.…”
Section: Introductionmentioning
confidence: 99%
“…All other variables, including hypertension, are still subject to debates. [1][2][3] The study of hypertension in SAH is problematic as patients, because of Cushing reflex, frequently show elevated blood pressure, irrespective of being or not hypertensive. 4 The aim of this study was to determine whether confirmed hypertension, prospectively diagnosed with target organ damage criteria, is an independent risk factor for SAH.…”
mentioning
confidence: 99%